2019
DOI: 10.1038/s41388-019-0703-z
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ promotes breast cancer stem cell self-renewal through an ILEI/LIFR signaling axis

Abstract: FAM3C/ I nterleukin- l ike E MT I nducer (ILEI) is an oncogenic member of the FAM3 cytokine family and serves essential roles in both epithelial-mesenchymal transition (EMT) and breast cancer metastasis. ILEI expression levels are regulated through a non-canonical TGFβ signaling pathway by 3’-UTR-mediated translational silencing at the mRNA level by hnRNP E1. TGFβ stimulation or silencing of hnRNP E1 increases ILEI tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 60 publications
2
73
0
Order By: Relevance
“…Additionally, the FAM3 family of created cytokines, ILEI-induced PDGF-C/PDGF-Rβ [42], or PDGF-Rα activation [43], enhance EMT and aggressiveness by increasing p-STAT3 via Src activation. Repression of hnRNP E1 by non-canonical TGF-β-induced Akt2 increases ILEI expression, and ILEI/ILFR promotes EMT and CSC generation [44,45].…”
Section: Critical Modulators Of the Jak2/stat3 Signaling Pathway In Emtmentioning
confidence: 99%
“…Additionally, the FAM3 family of created cytokines, ILEI-induced PDGF-C/PDGF-Rβ [42], or PDGF-Rα activation [43], enhance EMT and aggressiveness by increasing p-STAT3 via Src activation. Repression of hnRNP E1 by non-canonical TGF-β-induced Akt2 increases ILEI expression, and ILEI/ILFR promotes EMT and CSC generation [44,45].…”
Section: Critical Modulators Of the Jak2/stat3 Signaling Pathway In Emtmentioning
confidence: 99%
“…Kim et al have found that the IL-6/STAT3/ROS pathway can not only promote breast cancer progression and inflammation but also increase the formation of breast cancer stem cells [24]. Moreover, TGFβ-regulated FAM3C/ Interleukin-like EMT Inducer (ILEI), an oncogenic member of the FAM3 cytokine family, can mediate STAT3 signaling pathway to drive breast cancer stem cell formation and promote breast cancer progression [25]. In addition, TNFRSF1A, a gene encoding a transmembrane receptor for TNF-α, can be modulated by STAT3 and promote NF-κB signaling in breast cancer [26].…”
Section: Advances In the Study Of Stat3 Signaling Pathways In Breast mentioning
confidence: 99%
“…What's more, FAM3C has been shown to be strongly upregulated in several cancers including gastric cancer, melanoma, colon and breast cancer, oral and esophageal squamous cell carcinoma, essential for EMT and metastasis formation, and alter subcellular localization strongly correlating with poor survival [8,9,12,18,19]. It has been indicated that the FAM3C-YY1-HSF1 pathway exerted an important role in TGF β-triggered proliferation and migration of human breast cancer cells [11,20]. In addition, FAM3C is involved in retinal laminar formation in vertebrates and may relate to cell differentiation and proliferation during inner ear embryogenesis [21,22].…”
Section: Discussionmentioning
confidence: 99%